PENGARUH KONSUMSI MADU TERHADAP KENAIKAN HEMOGLOBIN PADA IBU HAMIL - Murtiningsih, Dewi; Satiyem, Satiyem (Poltekkes Kemenkes Maluku, 2023)
WHO determines normal Hb levels, the limit for pregnant women is 11.0 g for pregnant women. Honey is given to pregnant women because honey has the property of helping increase hemoglobin levels and helping the absorption of Fe. The aim of this research is to find out how honey affects increasing hemoglobin in pregnant women. This research is a quasi-experimental research with a pre test–post test design with control group. The population in this study were pregnant women in the Baturetno Wonogiri health center area. The sample in this study was 25 respondents from the control group and 25 respondents from the intervention group. Univariate analysis was carried out to determine the frequency distribution of maternal characteristics. In this study, the data that was obtained was then tested for normality using the Shapiro Wilk test. The results of the normality test obtained a p value > 0.05, so it was stated that the data was normally distributed. The results are said to be significant if the p value is <0.05, then H0 is rejected, which means there is a significant influence and if the p value is > 0.05, then H0 is accepted, which means there is no significant influence. Bivariate analysis of the independent t test resulted in a p value of 0.01 where the p value <0.05, it can be stated that it is significant for the variables studied. There is an effect of honey consumption on increasing hemoglobin in pregnant women, so from these results it is hoped that pregnant women will be recommended to consume blood supplement tablets and honey to increase hemoglobin levels and prevent anemia in pregnancy.